No foal yet - Haas, Jessie; Smith, Joseph A. (Joseph Anthony), 1936- (New York : Greenwillow Books, 1995)
Nora and her grandparents wait for their horse Bonnie to have her foal.
Wilson's Children
School Library Journal
Booklist
2.1
K-3
Keywords: Horses -- Juvenile fiction; Horses -- Fiction; Animals -- Infancy -- Fiction; Horses -- Fiction; Animals -- Fiction